Partner’s profile and unmet need for child limiting among women living with HIV in Ibadan, Nigeria (2021)
Introduction: In many African countries, the success of secondary prevention among reproductive-age women living with HIV (WLH) is affected by unmet need for family planning and marital contexts. The influence of the latter has not received adequate attention, especially among WLH. This study describes the level of unmet need for child limiting and the effects of partner’s characteristics among childbearing WLH in Ibadan, South-West, Nigeria. Material and methods: A cross-sectional study was conducted among married women of childbearing age attending antiretroviral treatment clinic, University College Hospital, Ibadan between November and December 2015. Data were analyzed using descriptive statistics and generalized linear models. Results: Of 781 women, 171 (21.9%) had unmet need for child limiting, while 14.2% and 45.7% have partners who were unemployed and in unskilled occupation, respectively. Controlling for partner’s characteristics, socio-economic and demographic variables, having a partner who is unemployed (OR = 3.51; 95% CI: 1.71-7.21), and unknown HIV status (OR = 2.09; 95% CI: 1.20-3.62), significantly increased odds of unmet need. Age between 45 and 49 years (OR = 4.34; 95% CI: 1.36-13.90), Christianity (OR = 1.75; 95% CI: 1.06-2.87), earning <= minimum wage (OR = 1.72; 95% CI: 1.07-2.76), and having more than two children ever born were also significant factors associated with unmet need. Conclusions: HIV care and treatment programs require innovative approaches to promote partner’s testing and economic empowerment of WLH to reduce the level of unmet need for child limiting among reproductive-age women living with HIV.